Key Digital Competences for Academic Training in University Students According to the Digcomp Model: A Study Based on Expert Judgement; [Competencias Digitales Clave Para la Formación Académica en Estudiantes Universitarios Según el Modelo Digcomp: Un Estudio Basado en Juicio de Expertos] - Silva-Quiroz, J (GTE-Educational Technology Group, University of the Balearic Islands, 2025)
Digital competencies (DC) are essential in higher education. This study identifies, through Expert Judgment selected by means of the Expert Competence Coefficient (ECC), which of the 21 DCs of the DIGCOMP framework are relevant for the academic development of university students. Thirty-three experts from Chilean, Latin American and Spanish universities were selected, of which 24 met the ECC above 0.8. These experts evaluated the CDs, the results were analysed using Lawshe s Content Validity Ratio (CVR), 16 competencies were identified as relevant, with representation from all areas, highlighting information and data literacy, and communication and collaboration. The average SCC was 0.815 with a standard deviation of 0.162, while the average argumentation coefficient was 0.874 with a standard deviation of 0.106. The results emphasize the relevance of integrating all areas of digital competence into university curricula, particularly the identified relevant competencies, given their impact on students academic and professional success. This study provides an empirical basis for designing educational programs that strengthen priority DCs, although the need for additional studies to measure the direct impact of each competency on academic training is recognized. © 2025 GTE-Educational Technology Group, University of the Balearic Islands. All rights reserved.